2016
DOI: 10.1177/2381336916661515
|View full text |Cite
|
Sign up to set email alerts
|

“I wonder if …”

Abstract: Current views of literacy have expanded to encompass how individuals in sociocultural systems make meaning as they ''read'' and ''write'' their world. From this view, the work of students involved in pursuing deeper understandings as they discuss course concepts is a literacy act. This study focused on the inquiry and questioning moves of graduate students as they participated in nine online classroom discussions about course concepts. A coding scheme adapted from several researchers interested in inquiry and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Research suggests that AODs offer opportunities for both engagement and reflection, as they leave time for students to think before they react. For example, it has been found that teacher candidates in online courses build community (Hou, 2015;Tseng & Kuo, 2014), reflect on their practice (Jones & Ryan, 2014;Whipp, 2003), pose clarifications (Fisch & Bennett, 2011) and develop deeper understanding through questioning (Williams et al, 2016). On the other hand, researchers have sometimes identified challenges to achieving meaningful discussion or making connections between knowledge and theory, especially in unmoderated forums (Ben-Peretz & Kupferberg, 2007).…”
Section: Discussion In Asynchronous Online Classesmentioning
confidence: 99%
“…Research suggests that AODs offer opportunities for both engagement and reflection, as they leave time for students to think before they react. For example, it has been found that teacher candidates in online courses build community (Hou, 2015;Tseng & Kuo, 2014), reflect on their practice (Jones & Ryan, 2014;Whipp, 2003), pose clarifications (Fisch & Bennett, 2011) and develop deeper understanding through questioning (Williams et al, 2016). On the other hand, researchers have sometimes identified challenges to achieving meaningful discussion or making connections between knowledge and theory, especially in unmoderated forums (Ben-Peretz & Kupferberg, 2007).…”
Section: Discussion In Asynchronous Online Classesmentioning
confidence: 99%